Antibiotics pollution in a typical reclaimed water receiving river in Hainan - Su Zhi (E3S Web of Conferences, 2025)
Although traditional sewage treatment processes can effectively remove pollutants such as nitrogen and phosphorus, they are difficult to remove new pollutants such as antibiotics. Antibiotics pose a threat to the environment when they enter rivers along with reclaimed water. To assess the impact of antibiotic discharge in reclaimed water, this study investigated 31 antibiotics in the Wanquan River, a representative river of reclaimed water in Hainan Province, China. The results showed that the discharge of reclaimed water will lead to an increase in the concentration and types of antibiotics in rivers, but it basically does not cause an increase in the ecological risks of antibiotics. This study supports the coordinated optimization of reclaimed water reuse and ecological safety.